DETERMINANTS OF SUCCESSFUL IMPLEMENTATION OF DIGITAL LITERACY PROJECT IN PUBLIC PRIMARY SCHOOLS IN BARINGO COUNTY, KENYA - Sutter, Florence; Kihara, Dr. Allan (Journal of Entrepreneurship and Project Management, 2019)
Purpose: The study aimed at finding out the determinants of successful implementation of digital literacy project in public primary schools in Baringo County in Kenya. The specific objectives of the study were to determine the effect of school leadership, information communication technology teacher competence, and teacher workload and information communication technology infrastructure. The study was founded on Technology Acceptance Theory, Resource Based Theory, Upper Echelons Theory and the Technology, Organization and Environment Model theories. This study adopted a descriptive survey research design. Methodology: The study targeted 612 stakeholders in the implementation of the Digital Literacy Project in public schools including the Ministry of education Science and Technology representative who is the Sub county Directors, the TSC Sub County Directors, curriculum support officers in the County, the Kenya Institute of Special Education Sub County coordinators, the Kenya Primary Schools Head Teachers Association Sub County coordinators, the Kenya National Union of Teachers Sub County coordinators and the head teachers of the public primary schools in Baringo county. Yamane formula was used to determine a sample size of 150 respondents. Structured questionnaire presented in likert scale were used in collecting primary data. Descriptive statistics such as percentages, mean and frequency was used to analyze the collected data. The study also used inferential statistics such as correlation and regression. Results: The study found that school leader of technology encourage use of technology in teaching and learning and help teachers establish goals to implementation of technology in achieving their instructional strategies and that school leader's interest; their commitment and championing implementation of ICT programs in schools positively influenced the whole process. The study concluded that school leadership had the greatest influence on implementation of digital literacy project in public primary schools in Baringo County in Kenya in Kenya followed by ICT infrastructure, then teachers ICT competence while teachers' workload had the least influence on the implementation of digital literacy project in public primary schools in Baringo County in Kenya. Contribution to policy and practice: The study recommends that the school leaders should increase their compliance with the various policies so as to ensure more effective integration of learning and teaching in primary schools and that school administration and stakeholders in education needs to be more supportive towards implementation of ICT programs.